Enhanced Ultraviolet Spontaneous and Lasing Emission Through Interface Engineering of Patterned Vertically Aligned ZnO Nanowires. Issue 19 (1st June 2022) - Guo, Zhen; Zhao, Dongxu; Li, Lin; Andreazza‐Vignolle, Caroline; Andreazza, Pascal; Zhang, Ligong; Zhang, Wei; Zhou, Lianqun
Abstract: Due to optical radiation losses, a high pumping threshold or low temperature is necessary for driving ultraviolet (UV) light emission devices, and surface/interface engineering method is one of the alternatives for tailoring photon behavior. Here, a fully integrated nanowire (NW) laser device is thus constructed, resulting in suppressed interface light loss. Enhanced UV spontaneous and lasing emission is observed due to adequate gain to compensate for the optical loss. Applying well‐aligned ZnO NW cavities, optimized UV spontaneous and lasing emission is realized, supporting an effective optical path through interface engineering for photon extraction. As proven by experimental results, through interface integration with Pt metal for ZnO NWs, 170% photoluminescence (PL) emission enhancement accompanied by 145% broaden emission spectra width in the UV region is obtained. It is also observed that more lasing modes appeare when excitation density is high enough, lasing modes interspacing of around 3 nm, and full width at half maximum of the modes <0.003 eV for the lasing device could be observed. The detailed optical simulation is proposed to understand the physical origin of internal mechanisms contributing to the optimized spontaneous and stimulated lasing emission behaviors. Abstract : Enhanced ultraviolet spontaneous and lasing emission is realized by reducing inner light loss from Fabry–Pérot (F‐P) cavities to substrate, through interface integration with Pt metal for ZnO nanowires, 170% photoluminescence emission enhancement and a lower laser threshold can be achieved with 7.69 times smaller when the Q factor becomes high enough.